A Comparative Analysis of High and Low Performing Schools in Agriculture in Eswatini - Alfred F. Tsikati; Sanele M. Motsa (Journal of International Agricultural and Extension Education, 2019)
Analysis of the school performance in external Agriculture examination showed that there were schools that consistently performed well and those constantly performing poorly in Eswatini. Unfortunately, there is no study that has sought to analyze the characteristics of the high performing and low performing schools in agriculture in Eswatini. Thus, the purpose of the study was to analyze the high and low performing schools in Agriculture in Eswatini. A comparative analysis targeting 27 schools: 15 high performing and 12 low performing schools was conducted. All the 38 teachers and 26 teachers from high and low performing schools respectively, participated in this study. A questionnaire was used in data collection. Three experts from the Department of Agricultural Education and Extension at University of Eswatini and two agriculture teachers validated the questionnaire. Thirty agriculture teachers who were not involved in the study were used in pilot testing to establish inter-item reliability using Cronbach’s Alpha and the reliability coefficient was .82. Data were analyzed using descriptive statistics. Findings revealed that high performing schools possessed the following features over low performing schools: motivation of learners to excel in academic work, practice farming in school garden, student making consultations with teachers, provision of extra lessons for students, monitoring class attendance and absenteeism, and teachers attending classes regularly. Also, the Ministry of Education and Training, headteachers, agriculture teachers and parents were more involved in high performing schools than in low performing schools. Therefore, the study recommended that special attention should be made to assist all stakeholders in low performing schools improve the academic performance.
Keywords: academic performance; agriculture; comparative analysis; low performing school; high performing school